Pengaruh beban kompaksi dan suhu sintering terhadap densitas dan sifat mekanik aluminium water atomized - Heru Sukanto (Universitas Sebelas Maret, 2018)
The powder size used in the research were maximum of 297mm and maximum of 105m resulted by water atomization. Both powder sizes were dry mixed by ratio of 65:35 %wt and was added by 1,25% wt of wax. Mixing was taking a place in steel cylinder with diameter of 2” roteted at 140 rpm for 2 hr. Green body was formed by pressing pressure of 280, 340, 400 and 435 Mpa. Sintering was conducted in argon and temperatures variation of 500, 550, 600 and 650oC for 2 hr.The results show thet sintering temperature change have no significant effects on density and mechanical properties while presing pressure have dominantly effects. Traverse rupture strength, density and hardness growth with increasing pressing pressure but they will decrease with increasing sintering temperature. The best increasing of mechanical properties was occurred at temperature sintering of 500oC and compaction pressure of 400 Mpa.